Drogi i bezdroża szkolnictwa wojskowego w Polsce - Kojkoł, Jerzy (Kultura-Społeczeństwo-Edukacja, 2012)
The article presents the history of the military higher education system, which is connected to the shaping of the Polish statehood as well as its present state. The structure of this type of education system was dependent on the e ectiveness of socio-economic, political and military activities of public authorities. However, it is only the November Uprising which is generally associated with the revolt of the o cers from the O cer Cadets School [Szkoła Podchorazych] in Warsaw. The changes which occur within the military education system on account of its adjustment to the requirements of the Act “Law on higher education” of 27 June 2005 are very positive. They accommodate military higher education institutions to the public system of higher education, they in uence the development and the quality of education in these institutions, they obliged them to implement the regulations arising from the National Quali cations Framework and to observe all the procedures arising from the legislations which are enacted in the domain of higher education by the competent public authorities.